Realism, Punishment, and Reform - Jones, Owen D. (2010)
Professors Donald Braman, Dan Kahan, and David Hoffman, in their article Some Realism About Punishment Naturalism, to be published in an upcoming issue of the University of Chicago Law Review, critique a series of our articles: Concordance and Conflict in Intuitions of Justice (http://ssrn.com/abstract=932067), The Origins of Shared Intuitions of Justice (http://ssrn.com/abstract=952726), and Intuitions of Justice: Implications for Criminal Law and Justice Policy (http://ssrn.com/abstract=976026). Our reply, here, follows their article in that coming issue. As we demonstrate, they have misunderstood our views on, and thus the implications of, widespread agreement about punishing the core of wrongdoing. Although much of their attack is therefore misplaced, important disagreements may remain concerning: whether there is a meaningful difference between core and non-core cases; whether judgments about core cases are less malleable than judgments about non-core cases; and whether imposing punishments perceived to be unjust imposes, in turn, significant costs on the criminal justice system. Which of the disputed views is correct can have important implications for the administration of criminal justice. Far from being anti-reformists, as accused, we argue that Reform Realism is the most effective path to bringing about needed reforms